Does corruption affect cooperation? A laboratory experiment - Raymundo M. Campos Vázquez; Luis A. Mejia (Latin American Economic Review, 2016)
In this paper, we analyze the nature of cooperation in different corruption regimes. In a laboratory experiment with university students in Mexico, individuals play first a corruption game and then a public goods game. The corruption game is divided into three groups: high- and low-monitoring scenarios as well as a control group not exposed to the game. The public goods game is divided into three groups: the standard game, a game with centralized punishment executed by an exogenously assigned leader, and a game similar to the second one, but adding the possibility of counter-punishment. There are four key results. First, there is more corruption in the low-monitoring group. Second, in the public goods game there is less cooperation in the low-monitoring group than in the group with more intensive monitoring. Third, the option of punishment increases cooperation, but the sensitivity to punishment is greater in the high-monitoring (low-corruption) group. Fourth, the option of counter-punishment of the leader decreases cooperation. Our results highlight the importance of corruption in decreasing trust and social capital and show the difficulty of promoting cooperation when corruption is prevalent.
Keywords: C90; D73; K42; 330; Corruption; Cooperation; Leader; Public goods; Laboratory experiment